Analysis of failure conditions for a dynamically loaded composite floor system of an industrial building - Berkowski, Piotr; Dmochowski, Grzegorz; Grosel, Jacek; Schabowicz, Krzysztof; Wójcicki, Zbigniew (Journal of Civil Engineering and Management, 2013)
Results of examination and analysis of cracks formation in a composite slab floor in an industrial warehouse hall is presented in the paper. During exploitation of the floor, on which lift trucks and presses worked, a lot of deep cracks occurred in the slab. In order to define characteristics of cracks and properties of concrete there were made different NDT examinations. Measurements of vibrations due to work of presses were also realized with aim to evaluate their possible influence on cracks formation. Static, dynamic and strength structural calculations were also made based on the model of continuous, multi-bay plate. They showed that applied slab reinforcement was sufficient and acting loads did not have to cause cracks. After 3D modelling of the building and taking into consideration the flexibility of main steel beams it was gained that in the RC floor slab over supports bending moments could occur nearly three times greater than calculated from the 2D model. Taking into consideration wrong structural model of the building led to over-loading of the floor slab, its cracking and caused a necessity of its strengthening.